2018
DOI: 10.1016/j.jocn.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The curcuminoid, EF-24, reduces cisplatin-mediated reactive oxygen species in zebrafish inner ear auditory and vestibular tissues

Abstract: Cisplatin is a widely used chemotherapy drug that can damage auditory and vestibular tissue and cause hearing and balance loss through the intracellular release of reactive oxygen species (ROS). Curcumin has anticancer efficacy and can also counteract cisplatin's damaging effect against sensory tissue by scavenging intracellular ROS, but curcumin's applicability is limited due to its low bioavailability. EF-24 is a synthetic curcumin analog that is more bioavailable than curcumin and can target cancer, but its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Some methods, through live imaging and forward genetic screens, can provide insight into the chemical and genetic mechanisms of ototoxicity as well as information about whether a protective cotreatment interferes with the therapy . The following are some examples of protective cotreatments discovered using this model: for radiotherapy for head and neck cancer, p38 inhibition; to mitigate cisplatin-induced ototoxiticy, quercetin, curcuminoids, CDK2 inhibition, or sirtuin 1 activation; for neomycin ototoxicity, melatonin, astaxanthin nanoemulsion; and recently discovered potential aminoglycoside-protective cotreatments. , The latter work resulted in repurposing a preapproved drug into clinical trials for aminoglycoside protection, demonstrating the utility for zebrafish to help advance discoveries that circumvent human ototoxicity.…”
Section: Ototoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some methods, through live imaging and forward genetic screens, can provide insight into the chemical and genetic mechanisms of ototoxicity as well as information about whether a protective cotreatment interferes with the therapy . The following are some examples of protective cotreatments discovered using this model: for radiotherapy for head and neck cancer, p38 inhibition; to mitigate cisplatin-induced ototoxiticy, quercetin, curcuminoids, CDK2 inhibition, or sirtuin 1 activation; for neomycin ototoxicity, melatonin, astaxanthin nanoemulsion; and recently discovered potential aminoglycoside-protective cotreatments. , The latter work resulted in repurposing a preapproved drug into clinical trials for aminoglycoside protection, demonstrating the utility for zebrafish to help advance discoveries that circumvent human ototoxicity.…”
Section: Ototoxicitymentioning
confidence: 99%
“…The pharmaceutical mechanism studies have revealed cell types, pathways, and genes involved in cardiovascular, , neuromuscular, neuronal, ocular, auditory, , and embryo-development toxicities. Those same studies introduce models by which safer compounds can be discovered by conducting SAR within or around a chemical series as has been lately shown for several chemotherapies. Equally important, those models can be used to interrogate species-specific mechanisms of toxicities, which is of great value for predicting clinical toxicity.…”
Section: Latest Advances and Future Directionmentioning
confidence: 99%
“…Cisplatin-induced oxidative stress Monroe et al (2018) reported that after 100 μM cisplatin treatment, the ROS increased dramatically in saccular and utricular tissues of zebrafish. The release of ROS was sharply elevated as cisplatin's concentrations increased to 500 μM (Monroe et al 2018).…”
Section: Cisplatinmentioning
confidence: 99%
“…Cisplatin-induced oxidative stress Monroe et al (2018) reported that after 100 μM cisplatin treatment, the ROS increased dramatically in saccular and utricular tissues of zebrafish. The release of ROS was sharply elevated as cisplatin's concentrations increased to 500 μM (Monroe et al 2018). The generation of ROS in the vestibular epithelium caused by cisplatin has been reported to cause vestibular HCs to undergo apoptosis (Tian et al 2013).…”
Section: Cisplatinmentioning
confidence: 99%
See 1 more Smart Citation